Imperial Satiety Protocol: A new non‐surgical weight‐loss programme, delivered in a health care setting, produces improved clinical outcomes for people with obesity. Issue 1 (15th October 2020) - Hameed, Saira; Salem, Victoria; Alessimii, Haya; Scholtz, Samantha; Dar, Owais; Miras, Alexander D.; Meeran, Karim; Bloom, Stephen R.; Ahmed, Ahmed R.; Purkayastha, Sanjay; Chahal, Harvinder; Tan, Tricia
Abstract: 'Imperial Satiety Protocol' (I‐SatPro) is a new multifaceted approach to weight loss for people with obesity (PwO), encompassing dietary advice, time‐restricted eating, physical activity and coaching to support behaviour change. Participants (n = 84) attended fortnightly I‐SatPro group sessions for 30 weeks, with 70% of participants completing. On completion at 30 weeks, the mean weight loss was 15.2 ± 1.1 kg (13.2 ± 0.8% from baseline, P < .0001), which was maintained to 52 weeks (16.6 ± 1.5 kg, 14.1 ± 1.2%, P < .0001). Weight loss was not associated with reduced energy expenditure. In participants with type 2 diabetes and pre‐diabetes (n = 16), glycated haemoglobin fell from 50 to 43 mmol/mol ( P < .01). Systolic blood pressure fell by 12 mmHg ( P < .0001). Triglycerides fell by 0.37 mmol/L ( P < .01) and high‐density lipoprotein rose by 0.08 mmol/L ( P < .01). Short Form‐36 (SF‐36) functioning and wellbeing scores increased in all domains post I‐SatPro intervention. For selected PwO, I‐SatPro delivers clinically meaningful weight loss, and the potential for long‐term health and wellbeing improvements.